2019
DOI: 10.3390/app9112280
|View full text |Cite
|
Sign up to set email alerts
|

New Evolutionary Algorithm for Optimizing Hydropower Generation Considering Multireservoir Systems

Abstract: In recent decades, solving complex real-life optimization problems has attracted the full attention of researchers. Dam and reservoir operation rules are considered one of the most complicated optimization engineering problems. In fact, the operation rules of dams and reservoirs are multisystematic and highly stochastic and have highly nonlinear system constraints due to the direct influence of environmental conditions: Therefore, these rules are considered highly complex optimization problems. Recently, metah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…where C is the penalty factor, ξ − i and ξ + i are penalties of training data of which the error is outside of the ε range, w i is the weight, x i is the input variable, and y i is the output variable. The values of w and b are calculated by Equation (2) and then substituted in Equation (1). There are multiple kernel functions for the support vector machine, and according to the previous studies, the radial kernel function (Equation (3) is an effective and widely used function.…”
Section: Support Vector Machinementioning
confidence: 99%
See 2 more Smart Citations
“…where C is the penalty factor, ξ − i and ξ + i are penalties of training data of which the error is outside of the ε range, w i is the weight, x i is the input variable, and y i is the output variable. The values of w and b are calculated by Equation (2) and then substituted in Equation (1). There are multiple kernel functions for the support vector machine, and according to the previous studies, the radial kernel function (Equation (3) is an effective and widely used function.…”
Section: Support Vector Machinementioning
confidence: 99%
“…Finally, monthly precipitation maps were generated based on the MLP-FRA model and Scenario 3 using the weighted interpolation method, which showed significant precipitation in spring and winter and a low level of precipitation in summer. The results of the present study showed that MLP-FRA has high capability to predict hydrological variables and can be used in future research.Consecutive droughts and increasing water demands mean that prediction and planning for the usage of precipitation are necessary for decision makers [1,2]. In addition, precipitation forecasting is necessary to prevent floods and construct flood-controlling structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The probable inflows are random than the dependable inflows. JA has been developed with the help of MATLAB for population size of 30 after performing sensitivity analysis for population sizes of 5,10,15,20,25,30,35,40,45, and 50. The optimal value is achieved for 150,000 FEs; the square root of the objective function achieved is 218.88 MCM.…”
Section: Mula Reservoirmentioning
confidence: 99%
“…The results proved superiority and robustness in comparison to other approaches. The Crow Algorithm (CA) proved its potential for reservoir operation optimization studies in [10]. It was implemented in the case of a multi-reservoir system in China for hydropower generation and was found to outperform other metaheuristic approaches by taking less computational time.…”
mentioning
confidence: 99%